2007
DOI: 10.1097/qad.0b013e3282703810
|View full text |Cite
|
Sign up to set email alerts
|

HCV/HIV co-infection, HCV viral load and mode of delivery: risk factors for mother-to-child transmission of hepatitis C virus?

Abstract: A total of 214 mother-and-child pairs were analysed; 55 (26%) were HCV/HIV co-infected. The probability of HCV transmission was three-fold higher for HCV/HIV-co-infected women (P = 0.05). Twelve children were HCV RNA positive at 1 year of age (MTC = 5.6%); three became HCV RNA negative between 12 (M12) and 18 months of age (M18) and recovered normal alanine aminotransferase levels. Circulating HCV RNA was found in 137 (69%) mothers. Mothers of infected children all displayed HCV viraemia (MTC = 8.8%): six chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 20 publications
1
47
2
4
Order By: Relevance
“…On the other hand, coinfected individuals are more likely to transmit HCV. The rate of vertical transmission of HCV is increased about threefold for coinfected mothers (95) compared to that for HCV-monoinfected ones; this effect may be limited to women with low HCV RNA levels (Ͻ10 6 IU/ml) (69). Percutaneous exposure of health care workers to blood from coinfected patients was also shown to increase the risk of acquiring HCV (35).…”
Section: Epidemiologymentioning
confidence: 99%
“…On the other hand, coinfected individuals are more likely to transmit HCV. The rate of vertical transmission of HCV is increased about threefold for coinfected mothers (95) compared to that for HCV-monoinfected ones; this effect may be limited to women with low HCV RNA levels (Ͻ10 6 IU/ml) (69). Percutaneous exposure of health care workers to blood from coinfected patients was also shown to increase the risk of acquiring HCV (35).…”
Section: Epidemiologymentioning
confidence: 99%
“…On the other hand, HBsAg reactivity is also associated with HCV seropositivity (Landes et al 2008), corroborating our finding that all HBsAg + patients in this study (2.5%) were also infected with HCV. Vertical transmission of HCV in Brazil was reported to be between 2.5-5.6% (Lima et al 2004), but higher rates have been reported elsewhere (Marine-Barjoan et al 2007). HCV viremia is an important risk factor for HCV vertical (Polis et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There was also a trend to lower HCV VL in this group, which may go some way to explaining this. Also, in a small French cohort of coinfected women (29% on HAART), rate of transmission did not differ significantly between children born by vaginal delivery or CS [200]. HAART should be given to all HCV/ HIV coinfected pregnant women, regardless of CD4 cell count or HIV VL because of the evidence of increased HIV transmission in coinfected mothers.…”
Section: In the Absence Of Obstetric Complications Normal Vaginal Dementioning
confidence: 99%